Kontribusi Sanitasi Lingkungan terhadap Kejadian Diare pada Balita di Daerah Pesisir Kota Kendari - Irma, Irma; Harleli, Harleli; Rompas, Helviani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Diarrhea is one of the causes of high rates of morbidity and mortality in children under five. The research aims to analyze the contribution environmental sanitation to the incidence of diarrhea in toddlers. This research is an analytical observational study with a cross sectional design with a population of all toddlers in the coastal area of ​​Abeli ​​District, Kendari City. The total sample was 110 people. Data was collected by conducting observations and interviews using questionnaires regarding the characteristics of respondents and environmental sanitation conditions, then univariate and bivariate analysis was carried out. The results of univariate analysis showed that the majority of family latrines (52.7%) were in the good category; The majority of SPAL (60.9%) is in the bad category and the majority of waste management (78.2%) is in the poor category. The results of statistical tests using Chi square with α = 0.05 showed that there was an influence of SPAL (ρvalue = 0.000) and waste management (ρvalue = 0.000) on the incidence of diarrhea in toddlers, and there was no influence of family toilet conditions (ρvalue = 0.121) on the incidence diarrhea in toddlers in the coastal area of ​​Abeli ​​District, Kendari City.